Evaluation of histologic localization of tumour-associated macrophages in invasive breast carcinoma and its association with prognostic parameters - Ahmad Affandi, Khairunisa; Sediqi, Mohammad Faiq; Muhammad, Siti Aeshah @ Naznin; A.Talib, Norlelawati; Che Alhadi, Shahidah; Abdullah, Suhaila (2021)
Introduction: There were 2.1 million new cases of breast cancer in 2018 worldwide. Recent cancer research has focused on the heterogeneous population of cells within the tumour microenvironment (TME). Non-cancerous cells surrounding the tumour and macrophages are the most abundant cells in TME. These macrophages, termed as tumour-associated macrophages (TAMs), are responsible for modulation of tumour growth and metastasis. This study aimed to evaluate the localization of TAMs infiltration within samples of breast carcinoma and its association with pathological prognostic parameters. Materials and Methods: In 128 paraffin-embedded cases diagnosed as invasive carcinoma, TAMs were immunostained with anti-CD163 antibody and the density of TAMs were counted within the tumour nests and tumour stroma. Results: TAMs were seen in both Tumour nests and tumour stroma. High CD163-positive stromal (p=0.0001) and nest (p=0.005) TAMs were significantly associated with higher tumour grades. High CD163-positive stromal TAMs were also significantly associated with negative estrogen receptor (ER) and progesterone receptor (PR) markers (p<0.0001 and p=0.001, respectively), and triple-negative subtype (p=0.002). Multivariate analysis showed that tumours with higher grades had higher TAMs infiltration in both tumour stroma (p=0.005; Odds Ratio (OR)= 13.917; 95% Confidence Interval (CI)=2.178-88.910) and nest (p=0.021; OR= 6.201; 95% CI=1.314-29.260). Conclusion: This research revealed that high TAMs infiltration in tumour stroma was associated with poor prognostic parameters. We also found that TAMs in tumour stroma and nests had different degrees of association with the clinicopathological parameters. Therefore, evaluation of TAMs will be a useful prognostic marker and may serve as potential cellular target for novel treatment modality in invasive breast cancers.